2000
DOI: 10.1007/bf02237437
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rectal mobilization and lateral ligaments division on colonic and anorectal function

Abstract: Rectal mobilization had a statistically significant effect on colonic function. Total and segmental colonic transit times doubled. The effects on anorectal function were not significant. Division of the lateral ligaments did not significantly influence postoperative functional outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
1
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(60 citation statements)
references
References 12 publications
2
52
1
5
Order By: Relevance
“…38,50 A number of studies have looked at the effect of the division or preservation of ligaments and are shown in Table 5 and Table 6.…”
Section: Role Of Division Of Ligamentsmentioning
confidence: 99%
“…38,50 A number of studies have looked at the effect of the division or preservation of ligaments and are shown in Table 5 and Table 6.…”
Section: Role Of Division Of Ligamentsmentioning
confidence: 99%
“…Bei unvollständiger Durchtrennung scheint die Rezidivrate erhöht, allerdings das funktionelle Ergebnis günstiger, da die postoperative Inkontinenz und Obstipation weniger ausgeprägt sind [16,18,23]. Die Reduktion postoperativer Entleerungsstörung durch eine Vermeidung der rektalen Mobilisation wird bei der ventralen Rektopexie diskutiert [6].…”
Section: Ausmaß Der Lateralen Rektummobilisationunclassified
“…Mobilisation zu postoperativen Entleerungsstörung führt [18,23], die Dissektion auf den ventralen Aspekt des Rektums im Spatium rectovaginale limitiert und ein anterior am Rektum fixiertes Netz am Promontorium angeheftet [6].…”
Section: Praxis Coloproctologyunclassified